Hubungan Parameter Laboratorium dengan Derajat Klinis COVID-19 pada Kehamilan - Nirmalasari, Rully Ayu; Surjadi, Lily Marliany; Maharani, Laksmi; Lisnawati, Yuyun; Mangun, Dhea (Jurnal Biomedika dan Kesehatan, 2023)
Background Pregnant women were one of the most susceptible groups because they are vulnerable to respiratory infection. They may get more severe symptoms due to their physiological changes during pregnancy including the immunological response. This study was performed to find whether there is an association between laboratory parameters (Hb, leukocytes, platelet, neutrophils, lymphocyte, monocyte, NLR, PLR and CRP) and the severity of Covid-19 infection in pregnant women. Methods This study is a retrospective cohort study using secondary data from patient’s medical records at Persahabatan General Hospital, Jakarta from March to June 2021. Results Pregnancy cases with COVID-19 in this study were in the mean of 29 year age. Most of them are in the third trimester of pregnancy. 80.5% from 67 patients have no- mild symptom while 19.5% have moderate to severe symptom. There are no difference in vital sign nor oxygen saturation at first admission. Lower level was found in the parameter of leukocyte, lymphocyte and monocyte.  Neutrophil, neutrophil-to-lymphocyte ratio and C-reactive Protein increase as the degree of severity increase.  The mean neutrophil in pregnant women with moderate to severe COVID-19 symptom was 80.49±7.47 while median NLR value was of 6.76 (2.73-18.71) . Conclusions Neutrophil, neutrophil-to-lymphocyte ratio and C-reactive Protein has associate significantly to severity symtomps of COVID-19 in pregnancy.